Ambrose Gwinett; or, a sea-side story: a melo-drama, in three acts - Jerrold, Douglas William, 1803-1857; Daniel, George, 1789-1864 (Salt Lake City, UT : Project Gutenberg, 2014)
"Ambrose Gwinett; or, A Sea-Side Story: A Melo-Drama, in Three Acts" by D. W. Jerrold is a theatrical work written in the early 19th century. This drama follows the tumultuous tale of Ambrose Gwinett, framed for murder and navigating through a web of love, deception, and betrayal. The play explores themes of innocence, social justice, and the consequences of one$1 (Bs actions, with a central focus on Gwinett as he grapples with the challenges of disproving his guilt and reclaiming his life. The beginning of the play sets the stage with Gwinett reminiscing about his life before his wrongful conviction. He recalls his humble beginnings in Canterbury and the unfortunate events that lead to his arrest, including a fateful encounter at an inn. As the narrative unfolds, we meet various characters, including Lucy Fairlove, who is caught in the middle of a love triangle that complicates Gwinett$1 (Bs plight. The opening scenes introduce themes of passion and jealousy, setting up an intricate plot that merges the personal with the tragic, as Gwinett is not only wrestling with external accusations but also with the turmoil of love and betrayal from those around him. (This is an automatically generated summary.)s
Release date is 2014-03-04
Transcribed from the [1828] John Cumberland edition by David Price. Many thanks to John Hentges for finding this, providing a copy for the transcription, and doing the background research
Keywords: English drama -- 19th century